The relationship between the microclimate and the landscape design of theme park [electronic resource] - Norsyazwani Md. Johari, 1987-; Hairul Nizam Ismail, supervisor (2014)
Thesis (Sarjana Sains (Perancangan Pelancongan)) - Universiti Teknologi Malaysia, 2014